Significance of Fixed and Variable Pay In Compensation Management: Exploring the Impact of Variable Pay on Compensation Management (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper is based on significance of fixed and variablepay in compensation management. Variable pay is a significant element of thedirect compensation package of a growing number of organizations. The trend istowards more organizations using variable pay and for these organizations toexpand eligibility and to increase the prominence of variable pay in the totaldirect compensation package.